Toward a Sociology of Artificial Intelligence: A Call for Research on Inequalities and Structural Change. (March 2021) - Joyce, Kelly; Smith-Doerr, Laurel; Alegria, Sharla; Bell, Susan; Cruz, Taylor; Hoffman, Steve G.; Noble, Safiya Umoja; Shestakofsky, Benjamin
This article outlines a research agenda for a sociology of artificial intelligence (AI). The authors review two areas in which sociological theories and methods have made significant contributions to the study of inequalities and AI: (1) the politics of algorithms, data, and code and (2) the social shaping of AI in practice. The authors contrast sociological approaches that emphasize intersectional inequalities and social structure with other disciplines' approaches to the social dimensions of AI, which often have a thin understanding of the social and emphasize individual-level interventions. This scoping article invites sociologists to use the discipline's theoretical and methodological tools to analyze when and how inequalities are made more durable by AI systems. Sociologists have an ability to identify how inequalities are embedded in all aspects of society and to point toward avenues for structural social change. Therefore, sociologists should play a leading role in the imagining and shaping of AI futures.